2009
DOI: 10.1021/nl802813f
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Giant Peptide Nanobelts

Abstract: Many alkylated peptide amphiphiles have been reported to self-assemble into cylindrical nanofibers with diameters on the order of a few nanometers and micrometer scale lengths; these nanostructures can be highly bioactive and are of great interest in many biomedical applications. We have discovered the sequences for these molecules that can eliminate all curvature from the nanostructures they form in water and generate completely flat nanobelts with giant dimensions relative to previously reported systems. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

32
452
5
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 434 publications
(491 citation statements)
references
References 57 publications
32
452
5
2
Order By: Relevance
“…45,46 Even if predictions cannot be done, it has been empirically observed that fibers with nanoscale chirality can be formed in glycolipid-based systems if specific sugar-to-lipid linkers like phenyl, 15 phenylamide 47 or amidopyridine 48 groups are used over simple ether bonding. 15 The former enhance hydrogen bonding 47,49,35 or π−π stacking whereas the latest only promote the formation of micelles.…”
Section: Introductionmentioning
confidence: 99%
“…45,46 Even if predictions cannot be done, it has been empirically observed that fibers with nanoscale chirality can be formed in glycolipid-based systems if specific sugar-to-lipid linkers like phenyl, 15 phenylamide 47 or amidopyridine 48 groups are used over simple ether bonding. 15 The former enhance hydrogen bonding 47,49,35 or π−π stacking whereas the latest only promote the formation of micelles.…”
Section: Introductionmentioning
confidence: 99%
“…Bundles of aligned PA nanofi bers were obtained, for example, by self-assembling PA within parallel channels (Hung and Stupp, 2007 ). By introducing hydrophilic amino acids in peptide segments, specifi c sequences of PA could self-assemble into nanobelts with fairly monodisperse widths in the order of 150 nm and lengths of up to 0.1 mm; these can be used as cell culture systems and drug delivery carriers (Cui et al , 2009 ). Nanofi brous scaffolds were also fabricated from self-assembly of β -sheet peptides containing phenylalanine for controlled release (Cui et al , 2009 ;Zhao et al , 2010 ).…”
Section: Molecular Self-assemblymentioning
confidence: 99%
“…By introducing hydrophilic amino acids in peptide segments, specifi c sequences of PA could self-assemble into nanobelts with fairly monodisperse widths in the order of 150 nm and lengths of up to 0.1 mm; these can be used as cell culture systems and drug delivery carriers (Cui et al , 2009 ). Nanofi brous scaffolds were also fabricated from self-assembly of β -sheet peptides containing phenylalanine for controlled release (Cui et al , 2009 ;Zhao et al , 2010 ). These studies proposed that the position of aromatic moieties is a signifi cant determinant for supramolecular self-assembling conformations.…”
Section: Molecular Self-assemblymentioning
confidence: 99%
“…The self assembly of biological molecules such as DNA and RNA, and a range of different proteins can assist in creating the nanobelts in fluidic solutions which can be used for many therapeutic applications [1]. Due to the importance of therapeutic applications, several kinds of polygon-shaped self assemblies have been developed by using the deoxyribonucleic acid [2,3].…”
Section: Introductionmentioning
confidence: 99%